Variability in HIV-1 Integrase Gene and 3′-Polypurine Tract Sequences in Cameroon Clinical Isolates, and Implications for Integrase Inhibitors Efficacy - Acharya, Arpan (Int J Mol Sci, 2020)
Integrase strand-transfer inhibitors (INSTIs) are now included in preferred first-line antiretroviral therapy (ART) for HIV-infected adults. Studies of Western clade-B HIV-1 show increased resistance to INSTIs following mutations in integrase and nef 3′polypurine tract (3′-PPT). With anticipated shifts in Africa (where 25.6-million HIV-infected people resides) to INSTIs-based ART, it is critical to monitor patients in African countries for resistance-associated mutations (RAMs) affecting INSTIs efficacy. We analyzed HIV-1 integrase and 3′-PPT sequences in 345 clinical samples from INSTIs-naïve HIV-infected Cameroonians for polymorphisms and RAMs that affect INSTIs. Phylogeny showed high genetic diversity, with the predominance of HIV-1 CRF02_AG. Major INSTIs RAMs T66A and N155K were found in two (0.6%) samples. Integrase polymorphic and accessory RAMs found included T97A, E157Q, A128T, M50I, S119R, L74M, L74I, S230N, and E138D (0.3′23.5% of samples). Ten (3.2%) samples had both I72V+L74M, L74M+T97A, or I72V+T97A mutations; thirty-one (9.8%) had 3′-PPT mutations. The low frequency of major INSTIs RAMs shows that INSTIs-based ART can be successfully used in Cameroon. Several samples had ≥1 INSTIs accessory RAMs known to reduce INSTIs efficacy; thus, INSTIs-based ART would require genetic surveillance. The 3′-PPT mutations could also affect INSTIs. For patients failing INSTIs-based ART with no INSTIs RAMs, monitoring 3′-PPT sequences could reveal treatment failure etiology.